Physicochemical profile of cream and derivatives obtained from mozzarella and prato cheese whey - BORGES, Wemerson; SANTOS, Givanildo de Oliveira; MEDEIROS, Jéssica Silva; FERNANDES, Patrick Bezerra; SILVA, João Antônio; LEÃO, Paulo Victor Toledo; MORAES, Ruthele; SILVA, Wanderson Rodrigues da; CAGNIN, Caroline; NICOLAU, Edmar Soares; SILVA, Marco Antônio Pereira da (Food Science and Technology, 2024)
Whey is an industrial residue obtained from the production of various cheeses and has the potential to be incorporated into other dairy products. Thus, the objective of the study was to promote whey skimming and standardization and to evaluate the physicochemical characteristics and color parameters of cream, regular butter, buttermilk, and clarified butter produced from whey resulting from the processing of mozzarella and prato cheese. Whey from the processing of mozzarella and prato cheese was skimmed and used for the production of regular butter and clarified butter. The physicochemical parameters and color parameters of whole and skimmed whey, regular and clarified butter, and buttermilk were analyzed. It was observed that whole whey from mozzarella processing had a higher fat proportion compared to prato cheese whey. It was possible to homogenize the whey samples considering the physicochemical parameters. The cream from whey, regardless of whether it resulted from mozzarella or prato cheese whey, only showed differences in color content, which was also the main difference between buttermilk and the regular and clarified butters obtained in this study. The similarities in the physicochemical parameters of regular and clarified butter suggest that these dairy products can be used in whey reutilization.